Addressing barriers to CRPD compatibility for advance planning provisions: an empirical study - Carter, Grace (2022)
This thesis identifies and addresses main barriers to compatibility with the Convention on the Rights of Persons with Disabilities (hereafter referred to as the CRPD) for advance planning provisions in England and Wales. The CRPD reimagines current mental capacity and mental health law, focusing on supporting the individual and respecting individual will and preference. Advance planning is one such explicit form of support. There are two potential uses for advance plans under the CRPD. These are to provide documented will and preference to be used when an individual has lost the ability to communicate, and to self-bind some decisions to overrule future will and preference during a mental health experience. The latter is by far the most contested. Despite ratification in 2009, we are yet to see meaningful legislative attempts at CRPD-compatible advance planning in England and Wales. Attempts are stifled by the retention of mental capacity assessments, their reliance on true self conceptions, and the tension between safeguarding vulnerable adults and the CRPD’s right to take risks and make mistakes. This thesis outlines these barriers to CRPD-compatibility and asks whether and how these barriers resonate with people who have experience of mental health difference. It also considers how identified barriers may be overcome to achieve greater compatibility while achieving the desired support. People with various mental health differences were invited to provide responses to these questions. 6 focus groups and 6 individual interviews were conducted, involving a total of 25 participants. Participants had a range of first and second-hand mental health experiences, including psychosis, PTSD, bipolar, schizophrenia, personality disorder, OCD, anxiety, depression, memory loss, dementia and Alzheimer’s. Main findings provide insight into self with mental health and how this offers a challenge to the true self conception often used to justify advance planning and restrictions to legal capacity. It supports existing research findings demonstrating a desire for self-binding by individuals who experience drastic changes in self and decision making during a mental health experience. Findings also indicate that the nature of mental health and how it impacts self influence participant opinions on self-binding, specifically whether self-binding should be available to all individuals and the scope of decisions an individual could be permitted to self-bind. Currently advance planning works the same for everyone, however these findings suggest a divergent approach may be more appropriate. Findings also indicate support for a non-absolutist adherence to will and preference when this adherence would lead to serious, direct self-harm leading to loss of life. New thinking is explored in relation to advance planning as a potential user-led alternative to mental capacity assessments and a way to opt into state intervention.